Main Components of The Semboro Variety of Siam Orange Peel Essential Oil Prepared Using Water Distillation Method - Budi Hariono; Risse Entikaria Rachmanita (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The maximum production potential for low quality oranges is 15% or 9,057 tons/year, the potential for orange peel waste is 50% of the total weight of oranges or the equivalent of 4,500 tons of orange peel waste The average yield of orange peel essential oil is 0.6%, resulting in a potential of 27 tons/year. The aim of this research is to obtain information regarding the best heating temperature in the distillation process and to identify the main components of Siam orange peel essential oil of the Semboro variety. The research was carried out using a laboratory-scale water distillation system, with a distillation flask capacity of 1 liter, with 150 g of orange peel as raw material at a distillation process heating temperature of 250°C and 300°C. The yields of 1.9 mL and 0.9 mL of Siam orange peel essential oil were obtained 1.083% and 0.513% respectively. The specific gravity of Siam orange peel essential oil is 0.855 g/cm3 and 0.886 g/cm3 respectively, the main components are 29 and 18 components respectively. An important finding of this research is that at a distillation process with heating temperature of 250°C, yields a limonene content of 16.10%, whereas heating at 300°C results in 7.69% limonene content. Keywords: Limonene; Low grade orange peel; Heating temperature; Quality essential oil.